An Application of a Game Development Framework inHigher Education. (12th April 2009) - Wang, Alf Inge; Wu, Bian
Abstract : This paper describes how a game development framework was used as a learning aid in a software engineering . Games can be used within higher education in various ways to promote student participation, enable variation in how lectures are taught, and improve student interest. In this paper, we describe a case study at the Norwegian University of Science and Technology (NTNU) where a game development framework was applied to make students learn software architecture by developing a computer game. We provide a model for how game development frameworks can be integrated with a software engineering or computer science course. We describe important requirements to consider when choosing a game development framework for a course and an evaluation of four frameworks based on these requirements. Further, we describe some extensions we made to the existing game development framework to let the students focus more on software architectural issues than the technical implementation issues. Finally, we describe a case study of how a game development framework was integrated in a software architecture course and the experiences from doing so.